Factors Associated with Pregnant Women's Knowledge about the Benefits of Iron Tablets in the Rasana’e Timur Community Health Center Area, Bima City - Faturahmah, Erni; Yuli Yanti (Jurnal EduHealth, 2023)
The global prevalence of anemia is estimated at approximately 51% (Arisman, 2015). In 2018, the incidence of anemia among pregnant women was 48.9%, with a notably higher prevalence of 84.6% observed in those aged 15-24 years (Riskesdas, 2018). Findings from the 2018 Basic Health Research indicate that 73.2% of pregnant women consumed iron tablets, but only 38.1% adhered to the recommended intake of up to 90 tablets. The research aimed to identify factors associated with maternal knowledge about the benefits of iron tablets. Employing a quantitative cross-sectional study design with a population of 120 respondents, a sample of 54 respondents was determined using the Slovin formula. The study was conducted at Rasana’e Timur Community Health Center in 2023, utilizing accidental sampling. Bivariate data analysis, employing correlation tests, revealed that age and knowledge were not significantly correlated (correlation coefficient = 0.133, P>0.05), while education and knowledge exhibited a significant correlation (correlation coefficient = 0.004, P<0.05). In conclusion, age did not demonstrate a correlation with knowledge, whereas education displayed a significant association with maternal knowledge. Recommendations include an increased focus on healthcare professionals providing education regarding the benefits of Fe tablets.